The diversity of land institutions in Europe - Johan Swinnen; Kristine Van Herck; Liesbet Vranken (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2014)
The creation of optimal land institutions attracted renewed attention in the 1990s because of its central role in the transition process in former Communist countries in the former Soviet Union and Eastern Europe and more recently because of largescale land investments in developing countries. This paper documents the existence of large variations in land institutions (markets and regulation) using current and historical data from Western and Eastern Europe. It then offers explanations for these differences and draws implications for the role and optimality of land institutions in development (with special reference to the current debate on large scale land acquisitions).
Keywords: 330; institutions; regulation; land markets; Europe